PENINGKATAN KAPASITAS PENGELOLAAN SDM MELALUI JOB COMPETENCY PROFILE ANALYSIS - Pramusiwi, Aloysia Desy; Harsiwi, Theresia Agung Maryudi (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service program aims to support the development of the human resource management system at PT Acasia Sanjaya Suryatama and the Direktorat Sekolah Sanjaya. The existing HR management system remains limited and primarily administrative in nature, resulting in several aspects of human resource management not being properly implemented due to operational constraints. To address these challenges, the Community Service Team from the Faculty of Business and Economics, Universitas Atma Jaya Yogyakarta, designed a workshop focusing on the formulation of a job competency profile analysis. The outcomes of the workshop, competency analysis, in-depth discussions and constructive feedback, significantly enhanced participants’ comprehensive understanding of the importance of identifying both core and functional competencies as key elements in achieving the organization’s overall objectives.